A Computer-Based Approach to Solving the Diophantine Equation $7^x-3^y=100$ - Dima, Andreea (The PUMP Journal of Undergraduate Research, 2022)
Assisted by Octave and by a website where one can find the order of a modulo m (here a and m are relatively prime natural numbers), I found a proof for showing that the diophantine equation $7^x - 3^y = 100$ has only the solution (x,y) = (3,5) in positive integers.